In defense of posthuman dignity. - Bostrom, N (2005)
Positions on the ethics of human enhancement technologies can be (crudely) characterized as ranging from transhumanism to bioconservatism. Transhumanists believe that human enhancement technologies should be made widely available, that individuals should have broad discretion over which of these technologies to apply to themselves, and that parents should normally have the right to choose enhancements for their children-to-be. Bioconservatives (whose ranks include such diverse writers as Leon Kass, Francis Fukuyama, George Annas, Wesley Smith, Jeremy Rifkin, and Bill McKibben) are generally opposed to the use of technology to modify human nature. A central idea in bioconservativism is that human enhancement technologies will undermine our human dignity. To forestall a slide down the slippery slope towards an ultimately debased 'posthuman' state, bioconservatives often argue for broad bans on otherwise promising human enhancements. This paper distinguishes two common fears about the posthuman and argues for the importance of a concept of dignity that is inclusive enough to also apply to many possible posthuman beings. Recognizing the possibility of posthuman dignity undercuts an important objection against human enhancement and removes a distortive double standard from our field of moral vision.